2020
DOI: 10.26434/chemrxiv.11821347.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Superior Hydrothermal Stability of Pd/SSZ-39 in Low Temperature Passive NOx Adsorption (PNA) and Methane Combustion

Abstract: We successfully synthesized uniform SSZ-39 with an average crystal size of about a micron. Pd (0.7 - 3 wt%) was supported on SSZ-39 with Si/Al ratio ~12. The as-synthesized materials were characterized by FTIR, XRD, Helium Ion Microscopy, HAADF-STEM imaging, 27Al, 29Si and H solid state NMR spectroscopic techniques. <br>FTIR studies with CO and NO probe molecules reveal that the 0.7 wt% Pd/SSZ-39 material with Si/Al ~12 has the majority of Pd dispersed atomically as isolated Pd(II) and Pd(II)-OH centers… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…We show the excellent performance of these materials under practically relevant conditions. Moreover, due to the presence of a specific Pd site in the FER micropores resistant to water hydrolysis during hydrothermal aging at 800 °C (and even 850 °C) in 10 % H 2 O/O 2 /N 2 mix for 16 hours, no changes in the adsorption of NOx occur, a feature that has not been previously achieved with any PNA material [6–19] . Although previously Pd/SSZ‐39 [14] showed stability of NOx uptake after aging at 800 °C, the NOx release profile broadened and shifted to higher temperatures which was not desirable (at CO levels ≈250 ppm in ref.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…We show the excellent performance of these materials under practically relevant conditions. Moreover, due to the presence of a specific Pd site in the FER micropores resistant to water hydrolysis during hydrothermal aging at 800 °C (and even 850 °C) in 10 % H 2 O/O 2 /N 2 mix for 16 hours, no changes in the adsorption of NOx occur, a feature that has not been previously achieved with any PNA material [6–19] . Although previously Pd/SSZ‐39 [14] showed stability of NOx uptake after aging at 800 °C, the NOx release profile broadened and shifted to higher temperatures which was not desirable (at CO levels ≈250 ppm in ref.…”
Section: Introductionmentioning
confidence: 94%
“…Conceptually, NOx is adsorbed at low temperature and released at temperatures when Cu/SSZ‐13 is active for SCR (200 °C and higher). As it was recently shown, the active sites in these Pd‐containing materials are isolated Pd ions located in the micropores of various zeolites [6–20] . Structure‐adsorption property relationships have been revealed for a range of Pd/zeolite materials (SSZ‐13, BEA, MFI, MWW, SSZ‐39) and guidelines for the preparation of high‐loadings of atomically dispersed materials have been disclosed [6–27] .…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…We previously found that Cu-SSZ-39 with the AEI structure showed superior HTS to Cu-SSZ-13 with the CHA structure, due to the more tortuous threedimensional 8 member-ring channels [15]. As PNA material as well as methane combustion catalyst, Khivantsev found that Pd/SSZ-39 showed excellent HTS and survived hydrothermal aging up to 815 °C without a significant loss of activity of PNA performance [16,17].…”
mentioning
confidence: 99%